Current status of goat husbandry and scope for improving its productivity in Bihar, Odisha and Uttar Pradesh - HEGDE, NARAYAN G; DEO, AVINASH D (The Indian Journal of Animal Sciences, 2017)
A study was undertaken in selected districts of Bihar, Odisha and Uttar Pradesh states, to understand the current status of goat husbandry and identify suitable interventions to enhance productivity and income of goat keepers. Approximately 87.2% families in the study area were living in poverty and 93% goat keeping families belonged to small, marginal or landless families. While 47.5% goat keepers owned less than 5 goats across the study area, over 73% goat keepers were small flock owners in Bihar and a majority of them were dependent on extensive grazing. This was predominant in Odisha where over 99% goat keepers were dependent on extensive grazing while in Bihar and Uttar Pradesh, less than 20% families were dependent on extensive grazing. PPR was the major disease, but FMD, enterotoxaemia, goat pox and HS were also reported with low intensity. Goat mortality was high at 33.5% in Bihar, 26.6% in Odisha and 20.6% in Uttar Pradesh. Goat husbandry was mainly looked after by women. Over 80% goat keepers sold their goats in their villages itself. The income from goats has been significantly low at ₹ 4,068 per family in Bihar, while it was slightly higher at ₹ 10,748 in Odisha. Assured breeding and health care services and financial support are needed to enhance the income of goat keepers. Hence, priority should be given to build their capacity for developing value chain and mobilise critical services for improving the production.